A note on the thyroid function of the pregnant females in the USA: data from NHANES 1999–2002 and 2007–2012. Issue 2 (7th February 2016) - Jain, Ram B.
Abstract : Thyroid dysfunction during pregnancy has been shown to be associated with adverse pregnancy outcomes. Consequently, this study was undertaken to assess the thyroid health of the pregnant females in the United States. Publically available data from National Health and Nutrition Examination Survey for the cycles 1999–2002 and 2007–2012 were analyzed for this purpose. Over 22% (SE: 5.7%) of the pregnant females based on the unweighted data in their first trimester had higher than the recommended levels of thyroid-stimulating hormone (TSH) or 2.5 mIU/L. Free triiodothyronine (FT3) and free thyroxine (FT4) levels decreased over pregnancy trimesters. Based on unweighted data, about 6% (SE: 2.6%) pregnant females were positive for thyroglobulin antibodies and 34.9% (SE: 5.2%) pregnant females were positive for thyroid peroxidase antibodies. Over 55% (SE: 3.5%) pregnant females based on the unweighted data were iodine deficient. As many as 41% (SE: 3%) first trimester pregnant females having TSH > 2.5 mIU/L is of concern. Future research should concentrate on developing educational and other materials that can advise pregnant females during their prenatal care and other appointments about the adverse effects of high TSH levels and what they can do to keep their TSH levels within the recommended levels.